1980
DOI: 10.1172/jci109771
|View full text |Cite
|
Sign up to set email alerts
|

Renal metabolism of amino acids and ammonia in subjects with normal renal function and in patients with chronic renal insufficiency.

Abstract: A B S T R A C T The net renal metabolism of amino acids and ammonia in the post absorptive state was evaluated in subjects with normal renal functioin and in patients with chronic renal insufficiency by measuring renal uptake and release, and urinary excretion of free amino acids and ammonia. In normial subjects the kidney extracts glutamine, proline, citrulline, and phenylalanine and releases serine, arginine, taurine, threonine, tyrosine, ornithine, lysine, and perhaps alanine. The renal uptake of amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
150
2
7

Year Published

1992
1992
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 330 publications
(178 citation statements)
references
References 28 publications
19
150
2
7
Order By: Relevance
“…The kidney synthesizes arginine from citrulline and a nitrogen donor, usually aspartic acid (Borsook & Dubnoff, 1941). In patients with chronic renal failure, it has been shown that a net citrulline uptake was balanced by an equal net arginine output, which on the overall was 40% less than in healthy humans (Tizianello et al, 1980). In our study, we show that plasma concentrations of arginine are independently and negatively associated with the presence of renal failure in critically ill patients.…”
Section: Discussionsupporting
confidence: 52%
“…The kidney synthesizes arginine from citrulline and a nitrogen donor, usually aspartic acid (Borsook & Dubnoff, 1941). In patients with chronic renal failure, it has been shown that a net citrulline uptake was balanced by an equal net arginine output, which on the overall was 40% less than in healthy humans (Tizianello et al, 1980). In our study, we show that plasma concentrations of arginine are independently and negatively associated with the presence of renal failure in critically ill patients.…”
Section: Discussionsupporting
confidence: 52%
“…As expected, individuals with chronic renal insufficiency have elevated plasma levels of citrulline [116,120,121]. Surprisingly, however, there is little or no decrease in plasma arginine in these patients.…”
Section: Renal Arginine Synthesismentioning
confidence: 70%
“…Approximately 60 % of net arginine synthesis in adult mammals occurs in the kidney [50,60], where citrulline is extracted from the blood and converted stoichiometrically into arginine by the action of ASS and ASL (Figure 2), which are localized within the proximal convoluted tubules [81,[112][113][114][115]. A tight correlation between renal citrulline uptake and renal arginine output has been elegantly demonstrated for both humans and rats [50,116]. Furthermore, in i o rates of arginine synthesis in adult rats are limited primarily by the amount of citrulline produced by other organs, such as the small intestine, rather than by the renal arginine biosynthetic capacity [50].…”
Section: Renal Arginine Synthesismentioning
confidence: 99%
“…In normal acid-base conditions the glutamine N extraction by the kidney is greater than the amount of ammonia that is produced, thus indicating that N supplied by glutamine extraction is more than sufficient to account for ammonia production (18,25,26). In the acidotic subjects we studied, the ratio of ammonia production to glutamine nitrogen extracted by the kidney was close to unity.…”
Section: Discussionmentioning
confidence: 80%